RETRACTED: Evaluation of Chronic Nanosilver Toxicity to Adult Zebrafish - Pecoraro, Roberta; Marino, Fabio; Salvaggio, Antonio; Capparucci, Fabiano; Di Caro, Gianfranco; Iaria, Carmelo; Salvo, Andrea; Rotondo, Archimede; Tibullo, Daniele; Guerriero, Giulia; Scalisi, Elena M.; Zimbone, Massimo; et al. (Frontiers in Physiology, 2017)
Nanotechnology is rapidly growing with nanoparticles produced and utilized in a wide range of commercial products worldwide. Among the different types of nanomaterials produced, silver nanoparticles (AgNPs) occupy a predominant position and they are used in electronics, clothing, food industry, cosmetics and medical devices. Nanosilver has also showed excellent performance in antibacterial application. Nowadays, the increasing use of AgNPs has put the evidence on their possible toxicity to the human health and the impact on the environment. This paper focus on adverse effects of AgNPs in adult of Danio rerio. Fishes exposed to increasing concentrations (8, 45, 70 g/l) silver nanoparticles (AgNPs, 25nm in average diameter) and after treatment for 30 days, was quickly euthanized in MS-222. We have evaluated bioaccumulation of AgNPs using ICP-MS and analyzed histological changes, biomarkers of oxidative damage and gene expression in the gut, liver and gills tissues of AgNPs-treated zebrafish. The histological analysis showed lesions of secondary lamellae of the gills with different degrees of toxicity such as hyperplasia, lamellar fusion, subepithelial edema, and even in some cases telangiectasia. Huge necrosis of the intestinal villi was found in the gut. No lesion was detected in the liver. The analysis revealed a high expression of metallothioneins 1 (MTs 1) in animals exposed to AgNPs compared to the control group. The ICP-MS analysis shows that the amount of particles absorbed in all treated samples is almost the same. We can affirm that AgNPs toxicity linked more to their size and state of aggregation than to their concentrations. Silver nanoparticles can damage gills and gut because they are able to pass through the mucosal barrier thanks to their small size. The damage is still reversible because it is not documented injury to the basal membrane.